PENGARUH ROE DAN DPR TERHADAP PBV DENGAN DER SEBAGAI VARIABEL INTERVENING - Eugenia Putri; Fredella Colline (Jurnal Akuntansi, 2021)
This study aimed to analyze the influence of Return on Equity (ROE) and Dividend Payout Ratio (DPR) on Price to Book Value (PBV) with Debt Equity Ratio (DER) as an intervening variable. This study used a sample of manufacturing companies sub-sector of various industry that were listed on Indonesia Stock Exchange (IDX) in 2015-2019. The statistical methods used in this research is Partial Least Square (PLS). The result showed that Return on Equity and Debt Equity Ratio have a significant effect on Price to Book Value, Dividend Payout Ratio doesn’t have effect on Price to Book Value, Return on Equity doesn’t have effect on Debt Equity Ratio, Dividend Payout Ratio have significant effect on Debt Equity Ratio, Debt Equity Ratio is not able to mediate the effect of Return on Equity on Price to Book Value, and Debt Equity Ratio is able to mediate the effect of Dividend Payout Ratio on Price to Book Value Keywords : Debt Equity Ratio, Dividend Payout Ratio, Price to Book Value, Return on Equity